One-hour post-load hyperglycemia combined with HbA1c identifies individuals with augmented duodenal levels of sodium/glucose co-transporter 1. (November 2021) - Fiorentino, Teresa Vanessa; Suraci, Evelina; De Vito, Francesca; Cimellaro, Antonio; Hribal, Marta Letizia; Sciacqua, Angela; Andreozzi, Francesco; Luzza, Francesco; Sesti, Giorgio
Abstract: Aims: Individuals with HbA1c-defined prediabetes (HbA1c 5.7–6.4%) and 1-hour post-load plasma glucose (1hPG) ≥ 155 mg/dl have an increased risk to develop type 2 diabetes (T2DM). T2DM is associated with a higher intestinal expression of sodium/glucose co-transporter 1 (SGLT-1) and glucose transporter 2 (GLUT-2). It is currently unsettled whether HbA1c-defined dysglycemic conditions combined to 1hPG ≥ 155 mg/dl are associated with changes in SGLT-1 and GLUT-2 duodenal abundance. Methods: SGLT-1 and GLUT-2 protein levels were assessed by western blot on duodenal mucosa biopsies of 57 individuals underwent an upper gastrointestinal endoscopy. Results: Compared with the normal group (HbA1c < 5.7%), individuals with HbA1c-defined pre-diabetes and diabetes exhibit no significant change in duodenal SGLT-1 abundance. Conversely, duodenal GLUT-2 levels were progressively increased in subjects with prediabetes and diabetes. Stratifying participants according to HbA1c and 1hPG we found that amongst subjects with HbA1c-defined normal or prediabetes condition those having 1hPG ≥ 155 mg/dl displayed higher duodenal levels of SGLT-1 as compared to their counterparts with 1hPG < 155 mg/dl; in contrast to GLUT-2 levels, which were similar between normal and with prediabetes subjects, regardless of 1hPG value. Conclusion: A value of 1hPG ≥ 155 mg/dl may identify a subset of individuals within HbA1c-defined glycemic categories having a higher duodenal abundance of SGLT-1.